A classical description of subnanometer resolution by atomic features in metallic structures. Issue 1 (7th December 2016) - Trautmann, S.; Aizpurua, J.; Götz, I.; Undisz, A.; Dellith, J.; Schneidewind, H.; Rettenmayr, M.; Deckert, V.
Abstract : Classical modelling of atomic scale corner sites, as present in realistic metal nano particles, reveals sub-nanometer lateral resolution in line with recent plasmon-enhanced spectroscopy experiments. Abstract : Recent experiments have evidenced sub-nanometer resolution in plasmonic-enhanced probe spectroscopy. Such a high resolution cannot be simply explained using the commonly considered radii of metallic nanoparticles on plasmonic probes. In this contribution the effects of defects as small as a single atom found on spherical plasmonic particles acting as probing tips are investigated in connection with the spatial resolution provided. The presence of abundant edge and corner sites with atomic scale dimensions in crystalline metallic nanoparticles is evident from transmission electron microscopy (TEM) images. Electrodynamic calculations based on the Finite Element Method (FEM) are implemented to reveal the impact of the presence of such atomic features in probing tips on the lateral spatial resolution and field localization. Our analysis is developed for three different configurations, and under resonant and non-resonant illumination conditions, respectively. Based on this analysis, the limits of field enhancement, lateral resolution and field confinement in plasmon-enhanced spectroscopy and microscopy are inferred, reaching values below 1 nanometer for reasonable atomic sizes.